Advanced building envelope components : comparative experiments - Stazi, Francesca (Butterworth-Heinemann, an imprint of Elsevier, 2019)
Advanced Building Envelope Components: Comparative Experiments focuses on the latest research in innovative materials, systems and components, also providing a detailed technical explanation on what this breakthrough means for building exteriors and sustainability. Topics include a discussion of transparent envelope components, including intelligent kinetic skins, such as low-e coatings, high vs. low silver content in glass, solar control coatings, such as silver vs. niobium vs. tin, and more. In addition, opaque envelope components are also presented, including opaque dynamic facades, clay lining vs. plasterboard and nano clayed foams.